2017
DOI: 10.3389/fpsyg.2017.01010
|View full text |Cite
|
Sign up to set email alerts
|

Interparental Conflict Relative to Suicidal Ideation in Chinese Adolescents: The Roles of Coping Strategies and Meaning in Life

Abstract: The aim of this study was to explore the paths between interparental conflict and Chinese adolescents’ suicidal ideation. Altogether 931 adolescents (Mage = 17.84, SD = 0.77, females = 531) completed the Dyadic Consensus Scale, Self-Report Coping Scale, Meaning in Life Questionnaire, and Positive and Negative Suicide Ideation questionnaires. Mediation analyses were conducted, focusing on the relations between interparental conflict and suicidal ideation along with coping styles and a sense of meaning in life. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 56 publications
3
11
0
Order By: Relevance
“…Another study found that married women were at the greatest risk of suicide by burning mostly due to quarrels with a family member, a relative, or a friend [36]. In addition, as reported in previous studies, family problems and cultural issues lead to self-immolation [7,30,31,35]. These factors and triggering events support the pre-motivation phase one of the IMV model [15].…”
Section: Discussionsupporting
confidence: 55%
“…Another study found that married women were at the greatest risk of suicide by burning mostly due to quarrels with a family member, a relative, or a friend [36]. In addition, as reported in previous studies, family problems and cultural issues lead to self-immolation [7,30,31,35]. These factors and triggering events support the pre-motivation phase one of the IMV model [15].…”
Section: Discussionsupporting
confidence: 55%
“…This is quite important because MiL is associated with strong motivation and plays an important role in developing a goal‐oriented life and predicting psychological and subjective well‐being in adolescents (Côté, ; Damon, ; Rathi & Rastogi, ). At the same time, it is a protective factor against negative patterns of behaviour, such as suicidal ideation, drug use, promiscuity, and eating disorders, among others (e.g., Brassai et al, 2011; Zhang et al, ). In addition, a lack of MiL is a risk factor for developing psychological distress and psychopathology (e.g., Butėnaitė, Sondaitė, & Mockus, ).…”
Section: Discussionmentioning
confidence: 99%
“…To a large extent, an authentic and goal-oriented life is the result of personal development during adolescence (e.g., Burrow, O'Dell, & Hill, 2010;Côté, 2002). Therefore, to develop a strong sense of MiL during adolescence could be a resource of resilience, a strong protective factor for successfully dealing with life's negative circumstances, psychopathological symptoms, and self-disturbances (Brassai, Piko, & Steger, 2015;Brouzos, Vassilopoulos, & Boumpouli, 2016;Fu & Law, 2017;Henry et al, 2014;Zhang, Li, Chen, Ewalds-Kvist, & Liu, 2017). Likewise, MiL is a strong predictor of wellbeing, mental health, and healthy behaviours both during adolescence (e.g., Wilchek-Aviad & Ne'eman-Haviv, 2018;Wilchek-Aviad, Ne'eman-Haviv, & Malka, 2016) and during adulthood (e.g., Lightsey, 2006;Ostrowski, 2015).…”
Section: Mil In Adolescentsmentioning
confidence: 99%
“…On the other hand, Kashfi et al found that self-immolation was most prevalent in the age group of 25 to 44 years old and stated that the highest cause of self-immolation attempts was due to family disputes [17]. In China, it was also found that family quarrel instigated suicidal ideation in young people [3]. Furthermore, Saadati et al revealed in their review that women were subject to selfimmolation more so than men.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, suicideattempts as the cause of mortality have increased across the world. Family conflicts may cause suicidal ideation in young persons in different ways such as malfunctioning coping strategies, lack of feeling of purpose in life [3] as well as lack of positive personality capital in forms of hope, selfefficacy, resilience and optimism about the future [4]. The countries of the former USSR have the highest suicide rates [5].…”
Section: Introductionmentioning
confidence: 99%